2022
DOI: 10.1590/fst.08721
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation efficacy of 405 nm light emitting diodes (LEDs) on Salmonella Enteritidis at different illumination temperatures

Abstract: Salmonella Enteritidis is the major cause of foodborne salmonellosis affecting human health. The light emitting diodes (LEDs) is a novel approach to inactivate of the foodborne pathogens. The aim of this study was to determine the antibacterial effect of 405 nm LEDs illumination on S. Enteritidis and S. Enteritidis PT4. The irradiance of the 405 nm LEDs was 27.7 mW/cm 2 . Bacterial cultures suspended in tryptic soy broth were illuminated by 10-watt LEDs at a distance of 4.5 cm for 24 hours at 4 °C, 25 °C and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…Photodynamic inactivation (PDI) by LEDs has recently attracted the attention by researchers as a potential application for food preservation that can minimize food pathogens posing risks to consumer health (Gao and Matthews, 2020;Kim et al, 2017b). There are many studies showing the high antibacterial activity of LEDs between 405-420 nm against a wide variety of bacteria (Du et al, 2020;Keyvan et al, 2022a;Kim et al, 2015;Maclean et al, 2009) . Our previous work developed a 405 nm illuminating LEDs system for bacterial inactivation and examined its time-and temperature-dependent antibacterial activity against S. Enteritidis and S. Enteritidis PT4.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Photodynamic inactivation (PDI) by LEDs has recently attracted the attention by researchers as a potential application for food preservation that can minimize food pathogens posing risks to consumer health (Gao and Matthews, 2020;Kim et al, 2017b). There are many studies showing the high antibacterial activity of LEDs between 405-420 nm against a wide variety of bacteria (Du et al, 2020;Keyvan et al, 2022a;Kim et al, 2015;Maclean et al, 2009) . Our previous work developed a 405 nm illuminating LEDs system for bacterial inactivation and examined its time-and temperature-dependent antibacterial activity against S. Enteritidis and S. Enteritidis PT4.…”
Section: Discussionmentioning
confidence: 99%
“…Carvacrol and curcumin were freshly dissolved each day in dimethyl-sulfoxide (DMSO) (Merck Millipore, 102952) (1:1, v: v) and later diluted in tryptic soy broth (TSB) (Oxoid, CM0876) before being applied. The minimal inhibition concentration (MIC) values of carvacrol (125.0 µg/mL) and curcumin (162.5 µg/mL) for S. Enteritidis and S. Enteritidis PT4, which were determined in our previous study (Keyvan et al, 2022a), were used to assess their photosensitizer activities in photodynamic inactivation experiments in this study. In the current study, we chose the amount of curcumin as two times the MIC value we found in the previous study.…”
Section: Photosensitizers and Chemicalsmentioning
confidence: 99%
See 3 more Smart Citations